Are Physicians Good Candidates For Recommending Diet? - S Hosseini; N Nayebi; B Amirkalali; N Seyedkhoei; R Heshmat (Tehran University of Medical Sciences, 2008)
Background: Primary prevention status and goals in 2010 are promoting healthy weight and eating habits and dietary manipulation considered in all reports to be the cornerstone of prevention and management of chronic diseases. Since in developing countries physicians are in the front line of responding patients' questions regarding their diet, we decided to evaluate their necessary nutritional knowledge for accomplishing this mission and to identify consideration for improving the paucity of nutrition education and the nutrition literacy in medical training program, we did the same education in medical students.Methods: Applied nutritional knowledge of 150 general, specialist and sub specialist physicians and 202 medical students was evaluated by structured self administrative questionnaire. Eighteen questions which could be self completed in less than 5 minutes were filled by each subject. Results: The percentage of physicians who gave dietary recommendations to their patients was 73% but the mean correct responds to questions were 3.73±2.15 and 5.87±2.14 out of 14 questions in physicians and medical students respectively. Conclusions: Our data show deficient applied nutritional knowledge of physicians is one of   the main problems of hospital malnutrition. As the same results were shown in medical students, this can not be due to forgetting what was learned but can be related to the quality of nutrition training.